PENDAMPINGAN PELAKU USAHA WARUNG DESA GIRIMUKTI KECAMATAN CIBATU KABUPATEN GARUT DALAM MELAKUKAN PEMASARAN MELALUI MEDIA SPANDUK - Syaifuddin Syaifuddin; Suca Rusdian (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2024)
Abstract. Assistance for stall entrepreneurs in Girimukti Village, Cibatu District, Garut Regency in marketing using banner media is an initiative aimed at increasing awareness of the importance of marketing strategies for MSMEs. Through this program, a survey was conducted to identify the main problems in marketing for stall businesses, which was then concluded that many business actors had not used banners as a promotional tool. Support from the community and STIE Yasa Anggana Garut KKN-PPM students made it possible to implement the mentoring program and put up banners as an example for other business actors. The choice of banners as promotional media in Girimukti Village was considered due to limited internet access in the area. The results show that banner installation is effective in increasing promotions, conveying information to potential consumers, and increasing the aesthetic value of business premises. In conclusion, this program can be considered an effective step in supporting the development and empowerment of MSMEs in the region.